Pemberdayaan Kelompok PKK dan Kampung KB dalam Implementasi Protokol Kesehatan, Vaksinasi, dan Pola Hidup Bersih Sehat untuk Memutus Penyebaran Covid-19 - Osman Syarief; Irmawartini Irmawartini; Dicki Bakhtiar Purkon; Ali Hamzah; Nandang Ahmad Waluya (Warta LPM, 2022)
The condition of the Covid-19 pandemic with various variant genetic mutations and severe manifestations can pose a risk of death with a relatively high transmission rate throughout the world. Moreover, the level of public awareness of compliance with health protocols and a clean and healthy lifestyle (PHBS), is still low from various survey results in Indonesia, including the Palasari and Cipadung Villages (Cibiru District), Bandung City, West Java. This community service activity aims to increase public health awareness and skills, especially community organization cadres as role models for other communities, such as PKK (Family Empowerment and Welfare) groups and KB (Family Planning) Villages with the Interprofessional Education (IPE) method conducted by a team of extension workers with various health science backgrounds with a series of activities that include: counselling on various health materials such as a clean and healthy lifestyle (PHBS), socialization of health protocols and self-isolation, mentoring on medical mask waste management, and how to make traditional herbal drinks as an immunomodulator (immunostimulant) to prevent/minimize the transmission of Covid-19. The entire counselling material was provided comprehensively to prevent the transmission of Covid-19 from various aspects, including aspects of nutrition, environmental health, 2000, and pharmaceuticals. The results achieved are the implementation of counselling on the introduction of Covid-19 and its various variants, prevention of Covid-19 from various health aspects, socialization of the application of health protocols, self-isolation, government vaccination programs, medical waste management, and how to make traditional drinks to improve the immune system in our body. The community service activities for Posbindu partner cadres in 2 Kelurahan were successfully implemented and could improve the understanding of health, attitudes, and behaviour of all Posbindu partner cadres by looking at the increase in the results of pre-test and post-test evaluations so that Posbindu partner cadres as part of change agents can distribute health information obtained to the public.